MODEL DINAMIS SISTEM KETERSEDIAAN DAGING SAPI NASIONAL - Harmini, Harmini; Asmarantaka, Ratna Winandi; Atmakusuma, Juniar (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2011)
The purpose of this paper is to assess whether the national program on beef self sufficiency could be achieved at 2014. A dynamic system model with Vensim computer program is applied. The model validated by Mean Absolute Percentage Error. The results shows high accuracies of the model. The assessment show that, first, the beef self sufficiency would not be achieved at 2014 if the program are treated and running as usual (Scenario I). Second, the beef self sufficiency would be achieved at 2015 if government increase the cow population by reducing the slaughter of local cows and expanding the cross breeding program through artificial insemination (Scenario II). Third, the beef self sufficiency would not be achieved at 2014 if the actual beef consumption are higher than the supply that produce through Scenario II (Scenario III). Another innovative solution for increasing local cow population is needed.